Exploring future scenarios for Latvia’s regional business incubators - Markus, Karlis; Rivza, Baiba; Rivza, Peteris (Business: Theory and Practice, 2025)
The research demonstrates that since 2007, the business incubator programs administered by the Investment and Development Agency of Latvia (LIAA) have significantly boosted regional entrepreneurship in Latvia. These programs provide essential support to young entrepreneurs, promote employment, stimulate entrepreneurship, and enhance the quality of life in the regions. Additionally, they increase export capacity and tax revenues. In this period, business incubators have been operated by the state, universities and private companies. The research analyzed future scenarios for the further development of regional business incubators in Latvia. Using the Analytic Hierarchy Process (AHP) and expert assessments, the study considered Latvia’s economic and social goals and strategic directions for regional development, underscoring the critical role of business incubators in promoting regional entrepreneurship and societal well-being. The research explored the possibility of transferring the administration of regional incubators to private companies, universities, or municipalities, which could impact regional economic development. A detailed assessment of previous LIAA programs concluded that various organizations, including private companies and universities, could effectively manage regional business incubators, fostering innovation and new product creation.